Efektivitas Pemanfaatan Teknologi Informasi dalam Sistem Penagihan Mega Distributor di PT Semen Indonesia (Persero) Tbk - Zahirah, Aishwarya Shafa; Vendy, Vicky (Politeknik Negeri Ambon, 2024)
This research aims to evaluate information technology's effectiveness in the Mega Distributor billing system, a business model with a centralized sales mechanism focusing on the billing process from the Operating Company (OpCo) to PT Semen Indonesia (Persero) Tbk. The use of information technology is the adoption of paperless in the Mega Distributor billing system, known as MD Paperless. This research uses a qualitative approach with a case study method conducted at PT Semen Indonesia (Persero) Tbk. The primary and secondary data were obtained through observation, documentation, and interviews with five informants. The results of this research show that the implementation of MD Paperless increases time efficiency and reduces operational costs. The risk of human error in the billing process is also significantly reduced. However, the implementation of MD Paperless has an obstacle, namely the existence of system problems from external parties. However, the company overcame these obstacles using a temporary manual scheme.